2020
DOI: 10.1007/s40685-020-00121-1
|View full text |Cite
|
Sign up to set email alerts
|

Revenue management systems as symbiotic analytics systems: insights from a field study

Abstract: Revenue management is a complex operational planning process involving predictive and prescriptive analytics. As real-world implementations strongly rely on the joint outcomes from both algorithms and analysts, we consider the revenue management system as an example of symbiotic analytics systems. This paper presents insights from a field study observing a natural experiment in revenue management. As a firm updates its automated revenue management systems, it also updates the related processes and the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Second, the opportunity to observe operational RM experts in situ, as described in Schütze et al (2020), is severely limited by company policy and labor councils. These seem to effectively prevent much empirical research on human analysts overruling analytics systems, with a few recent notable exemptions, such as Sun et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the opportunity to observe operational RM experts in situ, as described in Schütze et al (2020), is severely limited by company policy and labor councils. These seem to effectively prevent much empirical research on human analysts overruling analytics systems, with a few recent notable exemptions, such as Sun et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the broad diversity of possible RM system and process designs and the complexity of the related models create a wide range of possible system variants. In the light of this challenge, empirical studies, for example, as described in Zeni (2003) or Schütze et al (2020), might offer a better way of considering RM in its full complexity.…”
Section: Implications and Research Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, practical network RM often relies on manual forecast adjustments (Currie and Rowley, 2010;Schütze et al, 2020). However, previous research (Lawrence et al, 2006;De Baets and Harvey, 2020) has shown that the resulting judgemental forecasts can be biased and even superfluous.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%